SSP: a simple software process for small- size software development projects - Ochoa, Sergio (2006)
A large number of software development projects in Latin- American countries are small-size, poorly defined and time pressured. These projects usually involve under qualified people. Provided that well-known software development models have shown limited applicability in such scenario, developers usually carry out ad-hoc software processes. Therefore, the obtained results are unpredictable. This article presents a Simple Software Process (SSP) for small-size software projects involving under qualified people. The proposal is motivated by current practice in Chile. SSP proposes a step-by-step process which structures the development activities and it improves the process visibility for clients and team members. Furthermore, SSP formally includes “the user/client” as an active role to be played during the project. This process has been used in 22 software projects and the results are encouraging.